Research on Supernetwork Equilibrium about Deep Convergence of Enterprise Alliance for Breakthrough Innovation - Yumei Liu; Xin Wen; Xiangfei Meng (Discrete Dynamics in Nature and Society)
The realization of breakthrough innovation with high risk and uncertainty has always been the focus of the theory and practice of technological innovation. Based on the supernetwork theory, this paper constructs a supernetwork equilibrium model about deep convergence of enterprise alliance for breakthrough innovation and uses numerical simulation tools to find out the equilibrium conditions for deep convergence of enterprise alliance in different stages of breakthrough innovation. It is not only conducive to understand the process of enterprise alliance’s deep convergence in “Creativity-Research-Production-Sales” but also helpful to understand the roles that deep convergence in enterprise alliance can play in achieving breakthrough innovation. It not only expands the existing research on breakthrough innovation but also provides a scientific reference for the deep convergence of enterprise alliance in practice.